Further characterization and engineering of an 11-amino acid motif for enhancing recombinant soluble protein expression - Jiawu Bi; Elaine Tiong; Ying Sin Koo; Weibiao Zhou; Fong Tian Wong (Microbial Cell Factories)
Abstract Background Escherichia coli (E. coli) is a popular system for recombinant protein production, owing to its low cost and availability of genetic tools. However, the expression of soluble recombinant proteins remains an issue. As such, various solubility-enhancing and yield-improving methods such as the addition of fusion tags have been developed. This study focuses on a small solubility tag (NT11), derived from the N-terminal domain of a duplicated carbonic anhydrase from Dunaliella species. The small size of NT11 (< 10 kDa) lowers the chance of protein folding interference and post-translation removal requirement, which ultimately minimizes cost of production. Results A comprehensive analysis was performed to improve the characteristics of the 11-amino acid tag. By investigating the alanine-scan library of NT11, we achieved at least a two-fold increase in protein yield for three different proteins and identified key residues for further development. We also demonstrated that the NT11 tag is not limited to the N-terminal position and can function at either the N- or C-terminal of the protein, providing flexibility in designing constructs. With these new insights, we have successfully doubled the recombinant soluble protein yields of valuable growth factors, such as fibroblast growth factor 2 (FGF2) and human epidermal growth factor (hEGF) in E. coli. Conclusion The further characterisation and development of the NT11 tag have provided valuable insights into the optimisation process for such small tags and expanded our understanding of its potential applications. The ability of the NT11 tag to be positioned at either the N- or C- termini within the protein construct without compromising its effectiveness to enhance soluble recombinant protein yields, makes it a valuable tool across a diverse range of proteins. Collectively, these findings demonstrate a promising approach to simplify and enhance the efficiency of soluble recombinant protein production.